GENERATIONAL STRATIFICATION: ASPIRATIONS OF GENERATION NEXT - Taylor, Ruth; Dayaram, Kandy; Coffey, Jane; Holmes, Kirsten (The journal of contemporary issues in business and government, 2009)
Despite continuing recovery from the global financial crisis and improving employment levels, there is widespread consensus that Australia faces challenges of talent retention and skills shortages in both the public and private sectors. Currently, Generation Z—a demographic representing approximately 1.3 million Australians—is entering into higher education and the workforce. An understanding of the values and mindset of this generation is critical to the future Australian workplace in terms of delivering relevant education for both Generation Z and the workplace for which they are being educated. This paper uses qualitative research to identify the career aspirations, perceptions of work and family, and preference readiness for employment (particularly within the public sector) of Generation Z. The research found an increasingly conservative generation seeking high levels of flexibility and autonomy within the workplace. Implications for the public sector marketing itself as an employer of choice are discussed.